Electrosynthesis of a poly(1,5-diaminonaphthalene) - polypyrrole nanowire bilayer for trichlorfon insecticide biosensing - Anh, Nguyen Van; Huy, Nguyen Le; Quan, Do Phuc; Bich Lien, Vuong Thi; Dung, Nguyen Tuan; Lam, Tran Dai (Vietnam Journal of Chemistry, 2016)
In this study, an acetylcholinesterase enzyme biosensor was developed based on a bilayer of poly(1,5-diaminonaphthalene) and polypyrrole nanowire structures modifying carbon screen-printed electrodes (SPEs). A polypyrrole nanowire inner layer was electrodeposited on the surface of SPEs to enhance conductivity and specific areas. A poly(1,5-diaminonaphthalene) outer layer was used for immobilizing acetylcholinesterase through glutaraldehyde agent. On the basis of the inhibition of organophosphate pesticides on the enzymatic activity of acetylcholinesterase enzyme, the acetylcholinesterase-immobilized bilayer of the conductive polymer electrode was designed for electrochemical determination of trichlorfon insecticide, one of the popular organophosphate pesticides. Keywords. Acetylcholinesterase, biosensors, poly(1,5-diaminonaphthalene), polypyrrole nanowire, trichlorfon.